STRUGGLE IN USING ENGLISH TO COMMUNICATE FOR MYANMAR PEOPLE - Rita Hartati,; Carolina Silitonga,; Dhea Mutiana, (Journal of Innovation Research and Knowledge, 2022)
This study aims to determine the Struggle in using English to communicate for Myanmar people. By analyzing more deeply about the struggle and find some solution to the problem, we can asily understand how important English and how the struggle of the Asian country in using English. The research method is descriptive qualitative method. In collecting data, the researcher has done reading and observe the article and some news about the topic. Our data for this Mini Research assignment will be collected by reading some references from Asian Studies journals and news, selected journal for Critical Journal Review (CJR) and also from selected book from Critical Book Review (CBR). After collecting the data, the researcher will analyze them with resources review. The findings of the research related to the aspects of language that make Myanmar students get difficulties to communicate English, namely: It is different alphabetical order (script, letter, tone), different word order and grammatical structure. The solution to solve the difficulties is, Myanmar Government has been conducting seminar, workshop for English language programs, training and developing English Language for government officials, using English when discussing, negotiating during forums, seminars and workshop and most extensively used English for diplomacy and International affairs.